Shunt fault analysis methodology for power distribution networks with inverter-based distributed energy resources of the Korea Electric Power Corporation - Cho, Namhun; Yun, Sangwon; Jung, Jaesung (Renewable and Sustainable Energy Reviews, 2020)
Recently, the interconnection of distributed energy resources (DERs) has been observed to hinder the reliability of power supply. To solve this problem, the Korea Electric Power Corporation (KEPCO) has attempted to develop a practical fault analysis methodology for DERs that can be applied to distribution management system (DMS). This novel methodology to analyze the impacts of various DERs during shunt faults is presented in this paper. First, the basic concepts behind the proposed methodology are introduced. Then, the fault analysis methodology is introduced to determine the contributions of balanced and unbalanced DERs during shunt faults. Finally, the accuracy and feasibility of the proposed method are confirmed using SIMULINK and the IEEE 30-bus system, respectively. Based on the analyses, the proposed methodology is expected to be integrated with the rapidly developing distribution automation and management system of the KEPCO.
Keywords: Distributed Energy Resources; Distribution management systems; Electric power corporation; Fault analysis; Inverte-based distributed energy resource; Inverter-based; Power distribution network; Sequence networks; Shunt fault analyse; Superposition principle; Distribution management systems; Inverter-based distributed energy resources; Sequence network; Shunt fault analysis; Superposition principle